Experimental determination of partial charges with electron diffraction - Soheil Mahmoudi; Tim Gruene; Christian Schröder; Khalil D. Ferjaoui; Erik Fröjdh; Aldo Mozzanica; Kiyofumi Takaba; Anatoliy Volkov; Julian Maisriml; Vladimir Paunović; Jeroen A. van Bokhoven; Bernhard K. Keppler (Nature, 2025)
Abstract Atomic partial charges, integral to understanding molecular structure, interactions and reactivity, remain an ambiguous concept lacking a precise quantum-mechanical definition1,2. The accurate determination of atomic partial charges has far-reaching implications in fields such as chemical synthesis, applied materials science and theoretical chemistry, to name a few3. They play essential parts in molecular dynamics simulations, which can act as a computational microscope for chemical processes4. Until now, no general experimental method has quantified the partial charges of individual atoms in a chemical compound. Here we introduce an experimental method that assigns partial charges based on crystal structure determination through electron diffraction, applicable to any crystalline compound. Seamlessly integrated into standard electron crystallography workflows, this approach requires no specialized software or advanced expertise. Furthermore, it is not limited to specific classes of compounds. The versatility of this method is demonstrated by its application to a wide array of compounds, including the antibiotic ciprofloxacin, the amino acids histidine and tyrosine, and the inorganic zeolite ZSM-5. We refer to this new concept as ionic scattering factors modelling. It fosters a more comprehensive and precise understanding of molecular structures, providing opportunities for applications across numerous fields in the chemical and materials sciences.